1977
DOI: 10.1136/bmj.2.6090.789
|View full text |Cite
|
Sign up to set email alerts
|

Prospective trial of oestrogen and calcium in postmenopausal women.

Abstract: 789perience is thought to fit them for this more senior appointment. Nevertheless, the SCM (child health) should become fully aware of hospital activities and development through correspondence, attendance at clinical meetings, and by virtue of his position in the "cogwheel" paediatric division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
2

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(74 citation statements)
references
References 2 publications
4
68
2
Order By: Relevance
“…This observation supports the general concept that estrogen inhibits bone resorption in vivo (2,3,22,24,28,(35)(36)(37)(38), although in vitro studies showed OVX rats that were infused with 17,3E2 (C and F). Fourteen days after ovariectomy, rats were infused with PBS or 1 nM 1713E2 into the metaphyseal region of the femur for 8 days, 24 ,ul/day.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This observation supports the general concept that estrogen inhibits bone resorption in vivo (2,3,22,24,28,(35)(36)(37)(38), although in vitro studies showed OVX rats that were infused with 17,3E2 (C and F). Fourteen days after ovariectomy, rats were infused with PBS or 1 nM 1713E2 into the metaphyseal region of the femur for 8 days, 24 ,ul/day.…”
Section: Discussionsupporting
confidence: 69%
“…A major unanswered question is whether estrogen action on bone in vivo is direct or indirect (4,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). It has been suggested that in vivo estrogen promotes the systemic production of growth factors, so-called estromedins, or the removal of growth inhibitors, estrocolyons, elsewhere in the body (42).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has been supported by diverse evidence, including the inverse relationship between osteoarthritis and osteoporosis (6,7). Indeed, this inverse relationship has prompted the hypothesis that since estrogen replacement therapy protects against bone loss after menopause (2,(8)(9)(10)(11)(12)(13)(14), then estrogen therapy should also result in relatively higher bone mass and relatively stiffer bone. In theory, estrogen use could produce osteoarthritis by increasing bony stiffness, and, rather than deforming with weight-bearing, this stiff subchondral bone may transmit more force to the overlying cartilage, leading to cartilage damage (5).…”
mentioning
confidence: 99%
“…The mineralization of the skeleton undeniably decreases with age [22], and low BMD has been linked to an increased risk of fracture in elderly men and women [23][24][25][26][27][28][29], as well as in very elderly women [30,31]. Calcium supplementation has been shown to reduce the loss of bone [32], and increased consumption of calcium-rich dairy products (e.g., milk) has been found to provide an adequate source of dietary calcium, comparable to the results of other calcium supplementation strategies [33]. Even so, the association between dairy product consumption and bone health in elderly adults has not been firmly established [4,[7][8][9]34], and further investigation is warranted.…”
Section: Discussionmentioning
confidence: 99%